2019
DOI: 10.3390/ijtpp4020010
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-Based Multi-Point and Multi-Objective Optimization of a Turbocharger Radial Turbine

Abstract: This paper presents a gradient-based design optimization of a turbocharger radial turbine for automotive applications. The aim is to improve both the total-to-static efficiency and the moment of inertia of the turbine wheel. The search for the optimal designs is accomplished by a high-fidelity adjoint-based optimization framework using a fast sequential quadratic programming algorithm. The proposed method is able to produce improved Pareto-optimal designs, which are trade-offs between the two competing objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…When considering gradient-based optimisation, the adjoint method provides an effective way to calculate the gradients of an objective function with respect to design variables and alleviates the computational workload greatly (Jameson 1988; Giles & Pierce 2000; Economon, Palacios & Alonso 2013; Kline, Economon & Alonso 2016; Zhou et al. 2016), but the number of required adjoint computational fluid dynamics simulations is typically still prohibitively expensive when multiple optimisation objectives are considered (Mueller & Verstraete 2019). In gradient-free methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When considering gradient-based optimisation, the adjoint method provides an effective way to calculate the gradients of an objective function with respect to design variables and alleviates the computational workload greatly (Jameson 1988; Giles & Pierce 2000; Economon, Palacios & Alonso 2013; Kline, Economon & Alonso 2016; Zhou et al. 2016), but the number of required adjoint computational fluid dynamics simulations is typically still prohibitively expensive when multiple optimisation objectives are considered (Mueller & Verstraete 2019). In gradient-free methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The gradient-based optimization method is a search optimization algorithm, which takes the gradient of the objective function with respect to the design variables (DVs) as the optimization direction. The global optimization method and the gradient-based method were applied to turbine design, and shown that the gradient-based method calculated the Pareto front at a remarkably lower computational cost [19]. Unfortunately, the gradient-based optimization method is effective for the single objective function, but has limitations for obtaining the global optimal solution of multiple optimization objectives [20].…”
Section: Reference Design Variables Optimization Objectives Methods Optimization Algorithmmentioning
confidence: 99%
“…As the importance of including the structural integrity within the design and optimisation process became more apparent, work on turbomachinery adjoint structural optimisation to reduce the maximum stress has recently emerged, with a focus on radial turbines [23,24]. This was followed by a multidisciplinary approach involving aerodynamics and structural analysis and using decoupled adjoint optimisation for improving the efficiency of radial turbines either at design conditions [25] or at two operating points [26,27] while constraining the maximum von Mises stress [25,26] or its moment of inertia [27].…”
Section: Adjoint Optimisation Of Turbomachinerymentioning
confidence: 99%